A cardanol-based polybenzoxazine vitrimer: recycling, reshaping and reversible adhesion. Issue 44 (14th October 2020) - Trejo-Machin, Acerina; Puchot, Laura; Verge, Pierre
Abstract : This paper reports the development of the first vitrimer based on polybenzoxazines containing disulfide bonds and cardanol. Abstract : This paper reports the development of the first vitrimer based on polybenzoxazines containing disulfide bonds and cardanol. The synthesis of the monomer was carried out following a sustainable process, without any solvent and purification. The novel polybenzoxazine can be recycled, reshaped and (re)processed, thanks to a fast relaxation process (18 seconds at 120 °C) and low activation energy (64.5 kJ mol −1 ). Furthermore, the benzoxazine vitrimer shows significant and healable adhesive properties over short times and at low temperatures. These features support it also being considered in additive manufacturing applications, with the possibility of applying 3D printing technology, extending its application to many fields of materials.